2015
DOI: 10.1155/2015/640171
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic but Not CNS-Expressed Human C-Reactive Protein Inhibits Experimental Autoimmune Encephalomyelitis in Transgenic Mice

Abstract: We recently demonstrated that human C-reactive protein (CRP), expressed hepatically in transgenic mice (CRPtg), improved the outcome of experimental autoimmune encephalomyelitis (EAE), a murine model of multiple sclerosis (MS). The liver is the primary site of CRP synthesis in humans and in CRPtg mice but is also expressed by both at low levels in the CNS. To determine if CNS expression of human CRP is sufficient to impact EAE, we generated neuronal CRP transgenic mice (nCRPtg) wherein human CRP expression is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…We had previously shown that CRPtg undergoing EAE have delayed onset and reduced severity of disease compared to WT and that this beneficial effect of CRP is FcγRIIB-dependent ( 5 , 6 , 20 , 25 ), and herein we provide new evidence that this FcγRIIB-dependency extends to BMDCs in vitro . Moreover, although not all the observed effects of human CRP on BMDCs were supported by human FcγRIIB, CD11c-specific expression of human FcγRIIB was sufficient to fully reconstitute human CRP’s beneficial actions in EAE (Figure 7 ; Table 1 ).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…We had previously shown that CRPtg undergoing EAE have delayed onset and reduced severity of disease compared to WT and that this beneficial effect of CRP is FcγRIIB-dependent ( 5 , 6 , 20 , 25 ), and herein we provide new evidence that this FcγRIIB-dependency extends to BMDCs in vitro . Moreover, although not all the observed effects of human CRP on BMDCs were supported by human FcγRIIB, CD11c-specific expression of human FcγRIIB was sufficient to fully reconstitute human CRP’s beneficial actions in EAE (Figure 7 ; Table 1 ).…”
Section: Resultssupporting
confidence: 60%
“…Previously, we showed that human CRP protects CRPtg mice from EAE triggered either directly by immunization with MOG or indirectly by the transfer of MOG-specific T cells ( 5 , 20 , 25 ) and that this protection was FcγRIIB-dependent manner ( 6 ). Although human CRP can have direct effects on T cells ( 25 ), the initial evidence of CRP inhibiting EAE suggested that CRP most likely conferred protection by acting on an intermediary APC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the past decade, AE cases have been increasingly recognized due to the discovery of neuron-specific autoantibodies in the blood and/or cerebrospinal fluid (CSF) (Dubey et al, 2016). The pathogenic role of antibodies has been demonstrated by the passive transfer of autoantibodies to animal models, which recapitulated the effects of autoantibodies and the clinical manifestations of AE (Planaguma et al, 2015; Wright et al, 2015). However, the mechanisms through which these autoantibodies are generated and enter the central nervous system (CNS) remain elusive.…”
Section: Introductionmentioning
confidence: 96%
“…Several reports also indicate that CRP can promote the production of the anti-inflammatory cytokine IL-10, suggesting that elevated CRP levels may by a means to downregulate inflammation [ 17 , 18 , 53 , 54 ]. The effect of CRP may be further complicated by the relative levels of CRP in the circulation compared to the tissue or inflammatory site, as transgenic mice expressing CRP in lesions have differential responses to mice with high levels of systemic CRP [ 55 ].…”
Section: Discussionmentioning
confidence: 99%